Denationalisation de la littérature : un défi pour la littérature française - Almeida, José Domingues de (2010)
In the particular case of French literature, the post-national transition shows more painful because of the "literary specificity" and the cultural pact of the nation. We will try to enlighten the key-elements which characterize this evolution and this challenge.